(untitled) (Dhaka University Journal of Biological Sciences, 2020)
Self-compassion is a raising construct in the field of positive psychology. Evidence supported that self-compassion is an important factor in increasing psychological well-being and reducing symptoms of anxiety, depression and rumination. In the present study, authors determined the psychometric properties of the Bangla version of Self-Compassion Scale (SCS). The study was carried out in a sample of 160 adults, ranging from 18 to 28 years old. Although the original scale has 26 items, in item-total correlation analysis it was found that 24 items in the questionnaire were significantly correlated with total items, the rest two items consumed negative/low correlation (below 0.30). So, these two items were excluded from the Bangla version and 24 items were selected for the final version of the SCS. The internal consistency of the SCS was computed by Cronbach’s Alpha which was 0.83 and the split-half coefficient of the scale was 0.84. Thus the results support the Bangla SCS is suitable for use in Bangladeshi culture. Dhaka Univ. J. Biol. Sci. 29(1): 37-44, 2020 (January)